GIS In Epidemiology: Applications and Services - Bhatt, Bindu; Joshi , Janak P (National Journal of Community Medicine, 2012)
There is a growing understanding and appreciation regarding the power of health and health-related information in planning and implementing health programs. Given these points and the fact that most health information is tied in some way to geography, it is becoming increasingly important that health professionals, organizations, and communities create systems that empower them to really take advantage of the many different types of information that is available and that can be brought to bare on health issues and program management. There are countless layers or types of health and health-related data for a given population or place. GIS allow people to organize, visualize, and analyze these data layers more effectively. GIS and related spatial analysis methods provide a set of tools for describing and understanding the changing spatial organization of health care, for examining its relationship to health outcomes and access, and for exploring how the delivery of health care can be improved. Geographic information systems (GIS) provide ideal platforms for the convergence of disease-specific information and their analyses in relation to population settlements, surrounding social and health services and the natural environment. They are highly suitable for analyzing epidemiological data, revealing trends and interrelationships that would be more difficult to discover in tabular format. Moreover, GIS allows policy makers to easily visualize problems in relation to existing health and social services and the natural environment and so more effectively target resources. This study highlights the application and relevance of GIS for improving the efficiency of public health services.